Safety of Anticoagulation in Patients Treated With Urgent Reperfusion for Ischemic Stroke Related to Atrial Fibrillation. Issue 8 (August 2020) - Giustozzi, Michela; Acciarresi, Monica; Agnelli, Giancarlo; Caso, Valeria; Bandini, Fabio; Tsivgoulis, Georgios; Yaghi, Shadi; Furie, Karen L.; Tadi, Prasanna; Becattini, Cecilia; Zedde, Marialuisa; Abdul-Rahim, Azmil H.; et al.
Abstract : Background and Purpose: The optimal timing for starting oral anticoagulant after an ischemic stroke related to atrial fibrillation remains a challenge, mainly in patients treated with systemic thrombolysis or mechanical thrombectomy. We aimed at assessing the incidence of early recurrence and major bleeding in patients with acute ischemic stroke and atrial fibrillation treated with thrombolytic therapy and/or thrombectomy, who then received oral anticoagulants for secondary prevention. Methods: We combined the dataset of the RAF and the RAF-NOACs (Early Recurrence and Major Bleeding in Patients With Acute Ischemic Stroke and Atrial Fibrillation Treated With Non–Vitamin K Oral Anticoagulants) studies, which were prospective observational studies carried out from January 2012 to March 2014 and April 2014 to June 2016, respectively. We included consecutive patients with acute ischemic stroke and atrial fibrillation treated with either vitamin K antagonists or nonvitamin K oral anticoagulants. Primary outcome was the composite of stroke, transient ischemic attack, symptomatic systemic embolism, symptomatic cerebral bleeding, and major extracerebral bleeding within 90 days from the inclusion. Treated-patients were propensity matched to untreated-patients in a 1:1 ratio after stratification by baseline clinical features. Results: A total of 2159 patients were included, 564 (26%) patients received acute reperfusion therapies. After the index event, 505 (90%) patients treated with acute reperfusion therapies and 1287 of 1595 (81%) patients untreated started oral anticoagulation. Timing of starting oral anticoagulant was similar in reperfusion-treated and untreated patients (median 7.5 versus 7.0 days, respectively). At 90 days, the primary study outcome occurred in 37 (7%) patients treated with reperfusion and in 146 (9%) untreated patients (odds ratio, 0.74 [95% CI, 0.50–1.07]). After propensity score matching, risk of primary outcome was comparable between the 2 groups (odds ratio, 1.06 [95% CI, 0.53–2.02]). Conclusions: Acute reperfusion treatment did not influence the risk of early recurrence and major bleeding in patients with atrial fibrillation–related acute ischemic stroke, who started on oral anticoagulant. Abstract : Supplemental Digital Content is available in the text.